2015
DOI: 10.1021/acs.jafc.5b01064
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa, Blood Pressure, and Cardiovascular Health

Abstract: High blood pressure is an important risk factor for cardiovascular disease and cardiovascular events worldwide. Clinical and epidemiological studies suggest that cocoa-rich products reduce the risk of cardiovascular disease. According to this, cocoa has a high content in polyphenols, especially flavanols. Flavanols have been described to exert favorable effects on endothelium-derived vasodilation via the stimulation of nitric oxide-synthase, the increased availability of l-arginine, and the decreased degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…In this context, several epidemiological studies suggest a strong correlation between daily cocoa intake and better cardiovascular outcome in different population settings ( 19 21 ). Clinical interventional studies demonstrated a positive effect of flavanol-rich cocoa or chocolate intake on BP reduction and improvement in microvascular and macrovascular function ( 116 , 117 ). In vitro and in vivo studies identified increased NO availability, increased NO synthase activity, and inhibition of ACE as putative mechanisms of this beneficial effect ( 118 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several epidemiological studies suggest a strong correlation between daily cocoa intake and better cardiovascular outcome in different population settings ( 19 21 ). Clinical interventional studies demonstrated a positive effect of flavanol-rich cocoa or chocolate intake on BP reduction and improvement in microvascular and macrovascular function ( 116 , 117 ). In vitro and in vivo studies identified increased NO availability, increased NO synthase activity, and inhibition of ACE as putative mechanisms of this beneficial effect ( 118 ).…”
Section: Discussionmentioning
confidence: 99%
“…T2D is associated with functional and structural damages to the arterial wall that result in macrovascular complications and cardiovascular disease . Several interventional studies strongly suggest a potential role of cocoa intake in the maintenance of optimal vascular condition in healthy individuals and in situations of cardiovascular risk such as hypercholesterolemia and hypertension or during normal aging . Consequently, in the present study we evaluated the potential protective effect of cocoa on vascular stiffness and remodeling in a situation of high cardiovascular risk such as diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…The favourable effect of flavonoids on arteries is emerging and it has been recently described that flavonoids could be associated with improved measures of vascular function, and in particular with arterial stiffness . Accordingly, cocoa flavanols have been related to numerous cardioprotective effects, including lowering of blood pressure (BP), anti‐inflammatory and anti‐atherosclerotic effects, as well as antidiabetic actions . Despite these facts, the effect of cocoa flavanols on arterial function in a situation of high cardiovascular risk such as diabetes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, evidence suggests that cardiovascular effects are important in neuroprotection, specifically with regard to the impact on endothelial dysfunction (Jumar and Schmieder, 2016 ). To this end, cocoa flavonols improve vasodilatory capacity in high and low cardiovascular risk subjects (Heiss et al, 2003 ; Ferri et al, 2015 ; Jumar and Schmieder, 2016 ; Sansone et al, 2015 ). Given the obesity epidemic, and comorbid health problems in Mexico and the USA, cocoa and cocoa flavonoids may positively affect the pathophysiological mechanisms involved in insulin resistance and endothelial dysfunction, with potential benefits in the prevention of cardiometabolic diseases (Grassi et al, 2015a , b ).…”
Section: Neuroprotection: Chocolate An Ancient Friend and A New Playmentioning
confidence: 99%